Synthesis of Some Thiazolidinopyrazolines form Rhodanine - Pandey, Devendra; Nag, A.K. (Asian Journal of Chemistry, 2010)
Rhodanine is selected as a starting material due to the reason that at 5 position it contains an active methylene group which readily interacts with aromatic aldehydes to form benzylidene derivatives of rhodanine. The benzylidene compound derived from rhodanine possesses α : β unsaturated carbonyl group. They react with phenylhydrazine to form pyrazoline ring by cyclisation.